2004
DOI: 10.1007/s10434-004-1162-4
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Instability After Vascularized Fibular Harvest for Tumor Reconstruction

Abstract: Our series suggests that children with an age-length sum <16 should be considered for prophylactic tibiofibular synostosis creation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 27 publications
2
35
1
1
Order By: Relevance
“…When longer defects have to be reconstructed, the use of fibula graft or allograft may offer an advantage over ICBG. Harvesting of autogenous fibula is not without risk and complications [26] including foot drop, painful neuromas, ankle instability [28] and ankle valgus deformity [27]. The use of nonvascularized ICBG for reconstruction of postresection defects of the distal radius has several advantages over some of the other techniques described.…”
Section: Discussionmentioning
confidence: 99%
“…When longer defects have to be reconstructed, the use of fibula graft or allograft may offer an advantage over ICBG. Harvesting of autogenous fibula is not without risk and complications [26] including foot drop, painful neuromas, ankle instability [28] and ankle valgus deformity [27]. The use of nonvascularized ICBG for reconstruction of postresection defects of the distal radius has several advantages over some of the other techniques described.…”
Section: Discussionmentioning
confidence: 99%
“…33 Progression of the deformity is fostered by the development of a growth disorder at the lateral tibial epiphysis. 32,33 How the growth disorder develops is controversial. Nathan et al ascribes the growth disorder to anteromedial rotation of the proximal part of remnant distal fibula, impaction of the remnant fibula tip onto the tibial diaphysis, and lateral tibial physeal lysis, which could conceivably result in necrosis of the lateral tibial growth plate, permitting the relative overgrowth of the medial tibial physis versus the lateral tibial physis.…”
Section: Complicationsmentioning
confidence: 99%
“…The development of the valgus deformity is characterized by proximal migration of the fibula. 32,33,34 The proximal migration is thought due to the force transmission from the talus and muscle action of the peroneal muscles. 33 It is this proximal migration of the fibula that results in the ankle valgus deformity.…”
Section: Complicationsmentioning
confidence: 99%
“…Questionnaire results [1,3,30,36], disability scales [1,10,25], or gait analyses [3,25] have been reported in some studies, and disabilities such as pain, ankle instability, and inability to run have been described [1,3,10,18,25,30,32,36]. Other studies have attempted quantitative analyses of long-term side effects based on radiographs [2,10,14,28,30]. Most of these studies, however, focused on ankle deformities [2,10,28,30], and only one described thickening of the tibial lateral cortex [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have attempted quantitative analyses of long-term side effects based on radiographs [2,10,14,28,30]. Most of these studies, however, focused on ankle deformities [2,10,28,30], and only one described thickening of the tibial lateral cortex [14]. In contrast, experimental studies performed on animals have reported quantitative analyses of radius adaptation after ulna resection for pigs [15] and sheep [23,26].…”
Section: Introductionmentioning
confidence: 99%